Critical Review Zakat as Tax Deduction (Indonesia-Malaysia Comparative Study) - Eha Nugraha; Veranda Aga Refmasari; Alif Ilham Akbar Fatriansyah (Universitas Hayam Wuruk Perbanas, 2020)
This idea originated from the speech of the Minister of Finance at the 2nd Annual Conference of Islamic Finance in 2017 on the management of zakat and taxes. This paper critically discusses the regulation of income tax and zakat income in Indonesia and Malaysia. Furthermore, this paper aims to compare the treatment of zakat on personal income tax reporting with personal income tax in Malaysia. The research method used is design research that adopts the Plomp and Nieveen (2013) development model with adjustments, by collecting data through document studies, literature studies and in-depth interviews with zakat and tax practitioners. The results of the discussion show that Indonesia has not implemented zakat as a tax credit like Malaysia. Indonesia also does not yet have a national standard for zakat calculation.